Analysis of Published Criteria for Clinically Inactive Disease in a Large Juvenile Dermatomyositis Cohort Shows That Skin Disease Is Underestimated. Issue 9 (September 2015) - Almeida, Beverley; Campanilho‐Marques, Raquel; Arnold, Katie; Pilkington, Clarissa A.; Wedderburn, Lucy R.; Nistala, Kiran; on behalf of the Juvenile Dermatomyositis Research Group; Armon, Kate; Briggs, Vanja; Ellis‐Gage, Joe; Roper, Holly; Watts, Joanna; et al.
<x xml:space="preserve">Abstract</x> Objective The Pediatric Rheumatology International Trials Organisation (PRINTO) recently published criteria for classification of patients with juvenile dermatomyositis (DM) as having clinically inactive disease. The criteria require that at least 3 of 4 conditions be met, i.e., creatine kinase level ≤150 units/liter, Childhood Myositis Assessment Scale score ≥48, Manual Muscle Testing in 8 muscles score ≥78, and physician's global assessment of overall disease activity (PGA) ≤0.2. The present study was undertaken to test these criteria in a UK cohort of patients with juvenile DM. Methods We assessed 1, 114 patient visits for the 4 items in the PRINTO criteria for clinically inactive disease. Each visit was analyzed to determine whether skin disease was present. The Disease Activity Score (DAS) for juvenile DM was determined in 59 patients. Results At 307 of the 1, 114 visits, clinically inactive disease was achieved based on the 3 muscle criteria (but with a PGA of >0.2); rash was present at 65.8% of these visits and nailfold capillary abnormalities at 35.2%. When PGA ≤0.2 was one of the 3 criteria that were met, the frequency of skin signs was significantly lower (rash in 23.1% and nailfold capillary abnormalities in 8.7%). If PGA was considered an essential criterion for clinically inactive disease (P‐CID), patients with active skin disease were less likely to be categorized as having clinically inactive disease (a median DAS skin score of 0 [of a possible maximum of 9] in visits where the PGA was ≤0.2, versus a median DAS skin score of 4 in patients meeting the 3 muscle criteria [with a PGA of >0.2]; P < 0.001). Use of the P‐CID led to improvements in the positive predictive value and the positive likelihood ratio (85.4% and 11.0, respectively, compared to 72.9% and 5.1 with the current criteria). Conclusion There was a high frequency of skin disease among patients with juvenile DM who did not meet the PGA criterion for inactive disease but met the other 3 criteria. Incorporating PGA as an essential criterion for clinically inactive disease helps prevent the misclassification of patients with active skin disease.